Mapping of biodiversity hubs and key ecosystem services as a tool for shaping optimal areas for conservation. - Olivier Clement Gatwaza (Public Library of Science (PLoS), 2021)
Most National Parks (NP) and nature reserves in Rwanda have been established opportunistically in the early 1900s, without clear consideration of ensuring the protection to all threatened different taxonomical or functional groups, such as vegetation, invertebrates, fish, and birds. With the increasing conservation objectives, raised expectations into Protected Areas (PA), and within a more challenging environmental context, it is important to identify biodiversity hubs and key areas for Ecosystem Services (ES) to maximize the efficiency of conservation efforts by assisting priority areas under threats. To date, no comprehensive analysis, to the best of our knowledge has been done to assess both biodiversity and ES in Rwanda. This is a notable gap, considering that global-scale research suggests that the spatial overlap between biodiversity targets and ES is low. This study reports a nationwide assessment, mapping the richness of threatened species and three key ES Carbon Storage, Water Quantity, and Water Quality. Our analysis has shown that PAs are neither perfectly delineated to protect biodiversity nor key ES. The state of PAs offers a taxonomic protection bias in favor of mammals and birds but leaves many endangered species in other taxonomic groups in collapsing and unprotected small ecosystems scattered around the country. Rwanda's PAs cover important carbon stock but can do better at securing higher water balance regions and clean water sources. We propose an improvement of the NP system in Rwanda to help guide the economic development along a path of green growth and ensures the well-being of both people and nature. Locating biodiversity hubs and key ES can help to connect conservationists, local people, and governments in order to better guide conservation actions.